PENGARUH PENERAPAN BAHAN AJAR BERMUATAN KECERDASAN KOMPREHENSIF MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERHADAP KOMPTENSI FISIKA SISWA KELAS X SMAN 4 PADANG - Nadya Mahardika; Akmam Akmam; Gusnedi Gusnedi (Universitas Negeri Padang, 2016)
Learning outcome in physics is not optimal. Learning materials used by the students were still domina ted by materials which improves the competence of knowledge. Therefore, it is necessary learning materials to improve the competence of knowledge, attitudes, and skills of students. Learning materials that can be used is the learning materials contains comprehensiveo intelligence. The purpose of this research was to investigated the effect of applying the teaching materials contains comprehensive intelligence by using Inquiry learning model towards the competence of physics students grade X at SMAN 4 Padang. It was quasi-experimental research using Randomized Control Group Only Design. The population were the students grade X at SMAN 4 Padang who were registered in the Academic Year of 2015/2016. The technique sampling was by purposive sampling technique. The instruments were written test for competence of knowledge, observation sheet for competence of attitude and performance assessment sheet for competence of skills. The hypothesis was analized by using Chi Square at significance level of 0.05 and dk 1. Based on the results, it can be concluded that there are significant effect on the implementation of a learning materials contains comprehensive intelligence by using Inquiry learning model towards the competence of physics students grade X at SMAN 4 Padang